2018
DOI: 10.1002/jms.4058
|View full text |Cite
|
Sign up to set email alerts
|

MALDI imaging detects endogenous digoxin in glioblastoma cells infected by Zika virus—Would it be the oncolytic key?

Abstract: Recently, microcephaly cases have increased in Americas and have been matter of concern due to Zika virus (ZIKV) recent outbreak. Previous studies have shown that ZIKV‐infected progenitor neuronal cells present morphological abnormalities and increased rates of cell death, which may be indicators of microcephaly causes. As recent studies indicate ZIKV' tropism for brain cells, how would a glioblastoma (GBM) lineage behave under ZIKV infection, considering GBM the most common and malignant brain tumor in adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…In line with the toxic effects of ZVp observed in the present research, previous studies have shown cell survival rate and cycle alterations due to ZIKV infection in glioblastoma cells, where tumor cells infected with ZIKV showed cytopathic effects [7] and apoptosis [6]. In addition to caspase-3 activation, shown by Zhu et al, some studies have also shown that apoptosis induced by ZIKV might be associated with perturbation of Toll-like receptors-3 (TLR3) network [15] and consequent inhibition of Sonic Hedgehog and RAS-ERK signaling [16].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with the toxic effects of ZVp observed in the present research, previous studies have shown cell survival rate and cycle alterations due to ZIKV infection in glioblastoma cells, where tumor cells infected with ZIKV showed cytopathic effects [7] and apoptosis [6]. In addition to caspase-3 activation, shown by Zhu et al, some studies have also shown that apoptosis induced by ZIKV might be associated with perturbation of Toll-like receptors-3 (TLR3) network [15] and consequent inhibition of Sonic Hedgehog and RAS-ERK signaling [16].…”
Section: Discussionsupporting
confidence: 91%
“…According to the examples cited above, the focus of ZIKV scientific research has been upon its effects on neural progenitor/stem cells, mainly due to the evidences of viral neural tropism. However, new insights have emerged: ultimately, Zhu et al [6] and Lima et al [7] have considered ZIKV cell death associated with tropism for progenitor neural cells as a useful approach for neural tumor management. Their work showed that ZIKV is capable of infecting and effectively killing glioblastoma stem cells in comparison to normal neuronal cells, differently from other neurotropic viruses such as West Nile virus, which induces cell death in both normal and tumor neural cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature reports rely on the hypothesis that ZIKV promotes impaired NPCs growth, with associated apoptotic events, exerting similar effects over the systems of both newborns and adults 12 . The idea of interfering in the replication of cells with high metabolic rate has even elicited a whole new line of studies where ZIKV was used in an oncolytic-like strategy to treat aggressive gliomas, with results showing important cytopathic effects of the virus over the tumors 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados por Lima et al (2017) [3] indicaram o Zika vírus como uma estratégia para tratar o glioblastoma, o tipo histológico de glioma mais agressivo. Além do efeito citopático, o vírus também demonstrou possuir ação na inibição da via de mTOR [4].…”
Section: Introductionunclassified